Canales de distribución y su impacto en las ventas de artesanías de fibras de chambira de la comunidad El Chino, cuenca del río Tahuayo, 2021 - Catashunga Torres, Angel Ildefonso (2022)
The main objective of this research is to determine if the distribution channels have an impact on the level of sales of chambira fiber handicrafts in the community of El Chino, Tahuayo river basin, 2021. The specific objectives were: Determine if the current distribution channels of chambira fiber handicrafts of the El Chino Community, Tahuayo River Basin are inadequate; Determine if the sales and total income of chambira fiber handicrafts of the El Chino Community, Tahuayo River Basin are negative; and propose sales strategies to strengthen the distribution channels of chambira fiber handicrafts of the El Chino Community, Tahuayo River Basin. The artisans of the El Chino community in the Tahuayo river basin are entrepreneurs who produce and market handicraft products made from chambira fiber. This activity is their main source of income to meet their family's economic needs. This is a descriptive-correlational-transversal research with a non-experimental design; therefore, the behavior of the variables was described and the existing influence was established, for this purpose a population and sample of 20 artisans were taken, who were evaluated by means of a survey in Likert scale format, an instrument that was used to collect the pertinent data and information. The study concluded that the Distribution Channels generate impact on the sales of chambira fiber handicrafts in the El Chino Community, Tahuayo River Basin 2021; therefore, the hypothesis proposed in the research work was accepted, since it shows a significance level of 0.551, of correlation between both study variables.